A RELIGIÃO PAGÃ NA CIDADE DE AMMAIA (SÃO SALVADOR DE ARAMENHA, MARVÃO). PRAGMATISMO POLÍTICO E MULTICULTURALISMO FUNCIONAL - Mantas, Vasco Gil (Conimbriga, 2018)
The city of Ammaia, in the outskirts of Marvão, Portugal, has a reasonable epigraphic corpus through which it is possible to analyze important aspects of the Lusitanian-roman quotidian. This paper gathers available information on the urban religious practices in the Early Roman Empire, where indigenous and official cults coexisted, with a predominance of the cult to Jupiter, the highest expression of the roman legalism in the region. As expected, in an indigenous-majority city, the offerors of the monuments, mostly altars of classic design, reflect that origin and differing degrees of Romanization, in other words, the integrative acculturation that should be interpreted without anachronistic prejudice.